Evaluation of the Program to Improve the Welfare of Poor Families in Salassa Village, Curio District, Enrekang District - Yamin, Muhammad Nur; Herfida, Herfida; Ismail, Ismail; Pratiwi, Oky Nur (Jurnal Aktor, 2023)
This research aims to determine the Evaluation of the Welfare Improvement Program for Poor Families in Salassa Village, Curio District, Enrekang Regency. This research uses a qualitative method and produces descriptive data. Data collection is used by interview, documentation, and observation techniques. The data obtained from the research results are processed using interactive model analysis, namely data collection, data presentation, data condensation, drawing conclusions.The results of the study showed that the evaluation of the welfare family card (KKS) improvement program in Salassa Village, Curio District, Enrekang Regency, in general, had not been fully successful from the six (6) evaluation indicators, namely Efficiency, Responsiveness, Effectiveness, Adequacy, Equity and Accuracy. The Responsiveness indicator shows that the community's response is very good with the KKS program, effectiveness shows that it has not gone well because sometimes the distribution of aid is done once every 3 months, Efficiency shows that this assistance has not been said to be efficient because many still do not understand the details of the assistance received, Equity shows that it has not gone well because there are still many people who are classified as underprivileged getting assistance with the Prosperous Family Card, Adequacy shows that it is not enough because this assistance is not evenly distributed, Accuracy shows that this assistance is appropriate because this assistance is in accordance with existing procedures and names. assistance that comes out according to DTKS data. It is suggested that the process of updating the data must be further improved and preferably in the future it is better to prioritize the process of selecting data from RTSM/KSM so that there is no longer dependence on assistance and can utilize the assistance properly.